Peer Relationship Experiences Of Deaf And Hard-Of-Hearing Adolescents. (12th February 2020) - Terlektsi, E; Kreppner, J; Mahon, M; Worsfold, S; Kennedy, Colin R
Abstract: Deaf and hard-of-hearing adolescents (DHH) experience more peer problems and lower levels of friendships than their hearing peers. This study used a qualitative approach to identify their experiences of peer problems and factors influencing them. A sample of 30, 13–19 year-old DHH adolescents with a moderate to profound hearing loss, drawn from a population-based cohort study in which their receptive language and social–emotional skills had been assessed, underwent semi-structured interviews. Interviews were analyzed using thematic analysis. Participants reported that, overall, they had developed positive and rewarding relationships with their peers, notwithstanding their earlier experience of being bullied. Conflicts and infrequency of interaction in their friendships were mainly reported by girls. Adolescents with moderate hearing loss were identified as facing the same or even more barriers than adolescents with severe to profound hearing loss in making new friends. Implications for educational practice are discussed.